Analysis of the factors that have an impact on the destabilization of the columns of the Sal Cathedral of Zipaquirá, Cundinamarca - Galvis-Botía, Diana Rocío; Peñaranda, Nydia Genith; Jojoa-Muñoz, Jaime William (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
This article examines the factors that generate greater involvement in the stability of the chambers 360, 380 and 400 which constitute the space occupied by the Salt Cathedral of Zipaquirá, through the study of the physical and mechanical properties of the rock matrix. Thereafter we determine the solid properties and their possible behavior under vertical and horizontal stress state, as well as the loads acting on piers and columns, taking into account the conditions of the planes of discontinuities present in the elements of natural sustaining. Then we discuss some of the factors that generate the greatest instability to define which one is the most dominant and determine a method to mitigate it.